Implementing the OECD Principles on Water Governance Indicator Framework and Evolving Practices (OECD Studies on Water, 2018)
Water and its improved governance are critical for economic growth, social inclusiveness and environmental sustainability. Three years after the adoption of the OECD Water Governance Principles, this report takes stock of their use and dissemination. It provides a water governance indicator framework and a set of evolving practices for bench-learning, building on lessons learned from different countries and contexts.   Based on an extensive bottom up and multi-stakeholder process within the OECD Water Governance Initiative (WGI), these tools are conceived of as voluntary methodologies to be carried out at country, region, basin and/or city levels to improve water policies. The indicator framework is composed of a traffic light system based on 36 input and process indicators and a checklist with questions on a number of more specific governance conditions. The framework concludes with an action plan to help prioritise steps towards better design and implementation of water policies